On a stochastic linear dynamical system driven by a volterra process - Tran, Tuong Manh (Journal of Computer Science and Cybernetics, 2021)
The aim of this note is considering a dynamical system expressed by a Langevin equation driven by a Volterra process. An Ornstein - Uhlenbeck process as the solution of this kind of equation is described and a problem of state estimation (filtering) for this dynamical system is investigated as well.